Epistemology in Mulla Shadra’s Philosophy of Al-Hikmah Al-Muta’aliyah: an Analytical Review - Fitriyati, Intan Diana Fitriyati; Supriyanto, (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This study aims to analyze and delve into Mulla Shadra’s views on epistemology and how these views are related to the concept of al-Hikmah al-Muta’aliyah. Analytical methods are employed to understand the philosophical arguments put forth by Mulla ShadraThis study showed that Mulla Shadra introduced an epistemology based on the understanding of al-Hikmah al-Muta’aliyah as the highest source of knowledge. He proposed that true knowledge could be attained through spiritual experience and contemplation, which includes self-understanding and the relationship with God. Intuition and revelation also play a crucial role in Mulla Shadra’s epistemology, where he emphasizes the importance of intuitive understanding as a profound source of knowledge